The Alamo - Lace, William W. (San Diego, CA : Lucent Books, 1998)
An historical account of the first major battle in North America between the cultures of the United States, with its mainly British tradition, and that of Mexico, with its history of Spanish rule.
Includes bibliographical references (p. 87-90) and index.
Keywords: Alamo (San Antonio, Tex.) -- Siege, 1836 -- Juvenile literature; Alamo (San Antonio, Tex.) -- Siege, 1836.